Linguistic Risk-Taking: A Bridge Between the Classroom and the Outside World - Griffiths, Ed; Slavkov, Nikolay (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2021)
This article describes an initiative launched at a Canadian bilingual university in order to encourage L2 French and L2 English learners to take ‘linguistic risks’: authentic, autonomous communicative acts where learners are pushed out of their linguistic comfort zone. The initiative was operationalized through the development of a Linguistic Risk-Taking Passport, which contains 74 linguistic risks that students can take in their L2 across the university campus and in their everyday life. An analysis of interviews with participating teachers (n=6) and learner self-report data from completed passports (n=410) examines how the initiative was integrated into the classroom and which passport items were perceived by students as particularly high-risk. A cyclical process of risk-taking within a broad Task-Based Language Teaching (TBLT) framework is described in which risks are viewed as learner-selected tasks with a dynamic affective slant; risks can be used to connect classroom learning with real-life L2 use and vice versa. The data illustrate that linguistic risk-taking can help TBLT practitioners generate ideas on how to narrow the gap between the classroom and the real-world. The article concludes with a list of practical implications and suggestions for adapting linguistic risk-taking to other institutional contexts.